Analisis Minat Belajar Siswa SMK NWDI Pancor terhadap Cabang Olahraga Tenis Meja - Saputra, Imron Hadi; Hariadi, Hariadi; Suryadi, Lalu Erpan; Tamim, Muhammad Husni (Al-DYAS, 2025)
This study is motivated by the importance of identifying students’ learning interests in specific sports disciplines to support the development of physical education and extracurricular activities in schools. The objective of the research is to determine the level of student interest in table tennis at SMK NWDI Pancor. The study employed a survey method with a non-experimental approach, using a questionnaire distributed to 30 purposively selected students. The results show that 69% of students demonstrated a “good” level of interest in table tennis, 4% showed a “very good” level, 23% were in the “sufficient” category, and 4% fell into the “low” interest category. These findings indicate that, overall, table tennis is moderately well-liked among students, both as part of physical education and as an extracurricular activity. The study concludes that table tennis holds potential for further development within the school environment. The implications suggest that schools should design appropriate coaching strategies and provide adequate facilities to channel students’ interest toward skill development and achievement in this sport.